2014
DOI: 10.4103/2249-4863.130335
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant guillain-barré syndrome with myocarditis

Abstract: Guillain-Barré syndrome (GBS) represents a diverse spectrum of diseases, with variable pathophysiological mechanisms, clinical manifestation, presentation pattern, and degree of severity. We report a rare case of fatal fulminant GBS complicated with myocarditis during the course of illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A systematic study of the chief complaint of GBS is warranted for the following reasons. Firstly, chief complaints, the most significant symptoms reported by patients are not always in parallel with the results of physical examinations [ 4 , 5 ]. Empirically, for most of the time chief complaints reflect the most significant part of the clinical manifestations, and for some time, chief complaints contain symptoms that could not be found by physical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study of the chief complaint of GBS is warranted for the following reasons. Firstly, chief complaints, the most significant symptoms reported by patients are not always in parallel with the results of physical examinations [ 4 , 5 ]. Empirically, for most of the time chief complaints reflect the most significant part of the clinical manifestations, and for some time, chief complaints contain symptoms that could not be found by physical examinations.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Studies have reported that viral infection might be associated with Guillain-Barre syndrome and SPS. [17–22] Evidence of a respiratory viral infection was not found in this patient. Nevertheless, the inflammatory response to an infectious process should not be ignored, and a cytokine storm might be responsible for myocardial injury and nerve injury.…”
Section: Discussionmentioning
confidence: 76%